Patient behaviors during virtual clinic encounters in palliative care. Issue 1 (February 2023) - Agosta, Monica T.; Shih, Kaoswi Karina; Vidal, Marieberta; Zhukovsky, Donna; Bruera, Eduardo
Abstract: Telehealth use has accelerated since the COVID-19 pandemic and provided access for palliative care patients often facing challenges with travel and limited specialist availability. Our palliative care clinic at the University of Texas MD Anderson Cancer Center has rapidly adopted telehealth which continues to grow and provide care for patients since the pandemic, becoming a routine part of our center. While we strive to maintain consistency when it comes to compassionate, sensitive verbal and non-verbal communication, we have witnessed both advantages and disadvantages to telehealth services. We have come across unanticipated virtual visit challenges while trying to deliver quality care, surprising us from the other side of the camera. In this paper, we describe three cases of unexpected telehealth etiquette that posed new challenges in being able to complete virtual visits. We propose guidelines for setting patient etiquette for a productive telehealth palliative visit.